Influence of cervical muscle strength and pain severity on functional balance and limits of stability in elderly individuals with chronic nonspecific neck pain: a cross-sectional study - Shaker Hassan S. Alshehri; Ravi Shankar Reddy; Mohammad A. ALMohiza; Mastour Saeed Alshahrani; Batool Abdulelah Alkhamis; Hani Hassan Alnakhli; Ghada Mohammed Koura; Ajay Prashad Gautam; Debjani Mukherjee; Raee S. Alqhtani; Saeed Y. Al Adal; Abdullah Mohammed Alyami; et al. (BMC Geriatrics)
Abstract Background Chronic nonspecific neck pain (CNSNP) is a common musculoskeletal disorder, particularly in the elderly, leading to reduced cervical muscle strength, impaired functional balance, and decreased postural stability. This study investigated the correlation between cervical muscle strength, functional balance, and limits of stability (LOS) in elderly individuals with CNSNP. Additionally, it assessed the moderating effect of pain severity on the relationship between cervical muscle strength and these balance outcomes. Methods A prospective study included a total of 186 participants, including 93 with CNSNP and 93 asymptomatic individuals, were recruited. Cervical flexor and extensor muscle strength were assessed using an ergoFET hand-held dynamometer. Functional balance was measured using the Berg Balance Scale (BBS) and Timed Up and Go (TUG) test, while LOS were evaluated using the Iso-Free machine. Results Individuals with CNSNP exhibited significantly lower cervical flexor strength (32.45 ± 5.67 N vs. 40.75 ± 5.20 N, p < 0.001) and extensor strength (28.30 ± 6.05 N vs. 36.90 ± 5.90 N, p < 0.001) compared to asymptomatic individuals. Functional balance was also poorer in the CNSNP group, with lower BBS scores (47.85 ± 4.20 vs. 53.65 ± 3.85, p < 0.001) and slower TUG times (11.30 ± 2.05 s vs. 8.45 ± 1.80 s, p < 0.001). Cervical muscle strength showed moderate to strong positive correlations with LOS (r = 0.56 to 0.62, p < 0.001) and BBS (r = 0.48 to 0.53, p < 0.001). Pain severity significantly moderated the relationship between cervical muscle strength and functional balance (β = 0.20, p = 0.045) as well as LOS (β = 0.22, p = 0.038), suggesting that higher pain levels diminish the positive effects of muscle strength on balance. Conclusion Cervical muscle strength plays a crucial role in maintaining functional balance and postural stability in elderly individuals with CNSNP. Pain severity moderates the relationship between cervical muscle strength and balance outcomes, emphasizing the importance of integrating muscle strengthening and pain management in rehabilitation programs for elderly individuals with CNSNP to optimize postural control and minimize fall risk.